Lo stolto e l’intelligenza artificiale: Note a margine alla riedizione di un libro di Diego Lanza (Materiali di Estetica. Terza serie, 2021)
What is intelligence and what is stupidity? Why do we laugh at those who are stupid and why do we make fun of wise people? These are the fundamental questions in Diego Lanza’s book, Lo stolto. Di Socrate, Eulenspiegel, Pinocchio e altri trasgressori del senso comune, which appeared in 1997 and has just been republished by Petite Plaisance. The purpose of this article is to re-read the questions raised by Lanza’s book in the light of the current concepts of ‘intelligence’ and ‘artificial intelligence’.
Keywords: Artificial Intelligence; Stupidity; Robot; Creativity; Diego Lanza